Enzymatic and Genetic Characterization of Carbon and Energy Metabolisms by Deep-Sea Hydrothermal Chemolithoautotrophic Isolates of Epsilonproteobacteria - Takai, Ken (American Society for Microbiology, 2005)
The carbon and energy metabolisms of a variety of cultured chemolithoautotrophic Epsilonproteobacteria from deep-sea hydrothermal environments were characterized by both enzymatic and genetic analyses. All the Epsilonproteobacteria tested had all three key reductive tricarboxylic acid (rTCA) cycle enzymatic activities—ATP-dependent citrate lyase, pyruvate:ferredoxin oxidoreductase, and 2-oxoglutarate:ferredoxin oxidoreductase—while they had no ribulose 1,5-bisphosphate carboxylase (RubisCO) activity, the key enzyme in the Calvin-Benson cycle. These results paralleled the successful amplification of the key rTCA cycle genes aclB, porAB, and oorAB and the lack of success at amplifying the form I and II RubisCO genes, cbbL and cbbM. The combination of enzymatic and genetic analyses demonstrates that the Epsilonproteobacteria tested use the rTCA cycle for carbon assimilation. The energy metabolisms of deep-sea Epsilonproteobacteria were also well specified by the enzymatic and genetic characterization: hydrogen-oxidizing strains had evident soluble acceptor:methyl viologen hydrogenase activity and hydrogen uptake hydrogenase genes (hyn operon), while sulfur-oxidizing strains lacked both the enzyme activity and the genes. Although the energy metabolism of reduced sulfur compounds was not genetically analyzed and was not fully clarified, sulfur-oxidizing Epsilonproteobacteria showed enzyme activity of a potential sulfite:acceptor oxidoreductase for a direct oxidation pathway to sulfate but no activity of AMP-dependent adenosine 5′-phosphate sulfate reductase for a indirect oxidation pathway. No activity of thiosulfate-oxidizing enzymes was detected. The enzymatic and genetic characteristics described here were consistent with cellular carbon and energy metabolisms and suggest that molecular tools may have great potential for in situ elucidation of the ecophysiological roles of deep-sea Epsilonproteobacteria.